HELMINTH FAUNA OF TWO GECKO LIZARDS, HEMIDACTYLUS AGRIUS AND LYGODACTYLUS KLUGEI (GEKKONIDADE), FROM CAATINGA BIOME, NORTHEASTERN BRAZIL - Alves dos Anjos, Luciano (2011)
This study presented data on helminth fauna of two gecko lizards, Hemidactylus agrius and Lygodactylus klugei, from Caatinga biome in northeastern Brazil. It was found four helminth species parasitizing H. agrius, cistacanth of Centrorhynchidae (Acanthocephala) and the nematodes Physalopteridae (larvae), Parapharyngodon alvarengai (Pharyngodonidae) and Skrjabinelazia sp. (Seuratidade). The host Lygodactylus klugei presented two helminth species, one individual of Mesocoelium monas (Trematoda: Mesocoeliidae) in the small intestine and one encysted larvae of Physalopteridae (Nematoda: Physalopteridae) attached at stomach wall. The lizard species showed a low prevalence and low richness of helminths. Moreover, H. agrius presented a low intensity of infection. The foraging mode, arboreal habit and a restricted composition of diet could favoring the low prevalence, low infection rates and low richness of helminths found in these geckonid host species.